Obstetric and pregnancy-related factors associated with caesarean delivery in Bangladesh: a survey in Rajshahi district - Md Aslam Hossain; Md Reazul Karim; Md Golam Hossain; Abu Sayed Md Al Mamun; Md Abdul Awal; Jarin Sazzad (BMJ Open)
Objectives Caesarean section (CS) delivery is the most common operative obstetric procedure globally. The increasing trend of CS deliveries poses a significant threat to both child and maternal health. The adverse maternal outcomes associated with caesarean delivery represent a substantial public health concern worldwide. This study aimed to identify emerging obstetric and pregnancy risk factors and maternal outcomes associated with CS delivery among women in Rajshahi district, Bangladesh.Design This was a cross-sectional study.Setting Data were collected from 9 Upazilas with 233 community clinics of Rajshahi district, Bangladesh.Participants Multistage sampling technique was utilised for selecting sample from the population. A total of 540 mothers with a live infant were enrolled in the study. Descriptive statistics, χ2 test, logistic regression and ROC curve were used to analyse the data.Results The mean age of respondents was 26.28 years (SD 4.96); among them, the proportion of CS was 34.44%, with a higher proportion occurring in private clinics (82.8%) compared with public hospitals (17.2%). The likelihood of having a CS increased with factors such as insufficient sleep duration (p=0.002), oedema problems (p=0.014), inadequate supplements of micronutrients (p=0.009), severe headaches with blurred vision (p=0.028) and inadequate food consumption during pregnancy (p=0.032). The probability of experiencing obstetric fistula or postpartum anaemia (p=0.049) was higher among mothers who had a CS in their most recent live birth than mothers who had a vaginal birth.Conclusion The study found that having a CS increases the risk of maternal complications like an obstetric fistula or postpartum anaemia. Considering these results, it is recommended to urgently introduce carefully evaluated clinical practices to assess if vaginal delivery is possible. Counselling women about the delivery method is important to decrease unnecessary CS in Bangladesh.